PEMODELAN TIME-DEPENDENT BEHAVIOR MATERIAL DENGAN MENGGUNAKAN ELEMEN SPRING DAN DASHPOT - Hardi Wibowo (Diponegoro University, 2009)
To model behavior of material, there are two basic models of the material element i.e.: spring and dashpot.In many cases, time-dependent behavior of a material can not enough be used just one or two basic modelof the material element. To model time-dependent behavior of a material, combination of many basicmaterial elements should be used. The most important of long term behaviors of concrete material is creepbehavior. Many equation of creep prediction of the concrete materials have been proposed to manydesign specification and rule design, i.e.: American Concrete Institute (ACI), CEB/FIP 78 and 90, Bażant-Panula, Sakata, etc. This paper will be considering and demonstrating how to model creep compliancebased on creep coefficient as used by ACI-209 by using assembly of those basic material element